تحليل كتاب "البلاغة الوضيحة" وتناسبه لتعليم علم البيان في العصر الرقمي - أمليا, ديان رزقي; معصمة, معصمة; زليخا, ستي (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
The digital age is the age of technology and technology and is also called an industrial age, and an issue is reflected in the teaching of the science of statement, which is still using the old book, the book "Al-Balagah Al-Wadlihah", which has been twenty-four years to this day. This research aims to analyze the book "Al-Balagah Al-Wadlihah"and its suitability for teaching Ilmu Al-Bayan in the digital age. The methodology of this research is a qualitative approach and the method of its research is to analyze the content of the book "Al-Balagah Al-Wadlihah" and its suitability in the digital age, this research uses the technique of writing notation. Her research sources are the book "Al-Balagah Al-Wadlihah"and books, articles and research related to the teaching of rhetoric in the digital age. The researcher uses the analysis of her research using an analytical descriptive. The researcher has obtained from his research that the book "Al-Balagah Al-Wadlihah contains the teaching of Ilmu Al-Bayan and productivity, whatever it was not suitable for the need to teach the science of statement in the digital age, and it needs to shift in its content in terms of integrated with the progress of digital artificial intelligence New media via the Internet from its examples, research and model, as well as exercises, all of which correspond to the applicable curricula so that students get the maximum benefits. إن العصر الرقمي هو عصر التقنية والتكنولوجية ويطلق أيضا بعصر صناعي وتتجلى قضية في تعليم علم البيان التي لا تزال باستخدام الكتاب القديم وهو كتاب "البلاغة الوضيحة" الذى تمّ أربع وعشرين سنه إلى اليوم . تهدف هذا البحث على تحليل كتاب "البلاغة الوضيحة" وتناسبه لتعليم علم البيان في العصر الرقمي. وأما منهجية هذا البحث هي مدخل كيفي و أسلوب بحثها هو تحليل المحتوى كتاب "البلاغة الوضيحة" وتناسبه في العصر الرقمي، تستخدم هذا البحث تقنية تدوين الكتابة. أما مصادر بحثها هو كتاب "البلاغة الوضيحة" وكتب والمقالات والبحوث ما يتعلق بتعليم علم البيان في العصر الرقمي. عينت الباحثة تحليل بحثها باستخدام وصفية تحليلية. وقد حصلت الباحثة من بحثه بأن كتاب "البلاغة الوضيحة" "البلاغة الوضيحة" تحتوي على تعليم البلاغة النمطية والإنتاجية مهما كان لم تناسب على حاجة تعليم علم البيان في العصر الرقمي وهو يحتاج إلى التحول في محتواه من حيث تتكامل بتقدم الرقمي بالذكاء الاصطناعي الوسائط الجديدة عبر الانترنيت من أمثلتها وبحثها ونموذجها وكذلك تمريناتها، كلها تتوافق مع المناهج الدراسية المعمول بها حتى يحصل الطلاب على أقصى قدر من الفوائد.